Extraction of chitin from mud crab (Scylla serrata) shells using choline chloride - urea based deep eutectic solvent. - Menez, Ken N.
Chitin is a natural polysaccharide obtained from the exoskeletons of animals such as crustaceans, mollusks, and insects, or the cell walls of fungi. It is typically used in several applications as chitosan, which is a derivative obtained from deacetylating or removing the acetyl groups that constitute chitin. This produces a flexible polymer with variable properties such as solubility, tensile strength, cytotoxicity, etc., based on the degree of its deacetylation (DDA). The most common industrial process used to both extract chitin and produce chitosan utilizes high concentrations of acid and alkali, called chemical extraction. This process has the disadvantage of producing large environmental waste, as well as easily degrading the quality of chitin products. Recently, green solvents such as deep eutectic solvents are being used as extraction medium for different materials, including chitin. The products are generally much more environmentally stable and reusable compared to chemical extraction. In this study, a mixture of choline chloride and urea was used as a basis for a deep eutectic solvent to extract chitin from mud crab (S. serrata) carapaces. The produce chitin was compared against acid-based derived chitin from the same crab species, though parameters such as DDA, thermogravimetric analysis (TGA), and FTIR characterization. The DES extraction had significantly faster reaction time for its whole process (6 h) compared to acid-base/chemical extraction, and produced chitin with a lower DDA (92.92%) and higher DTG peak temperature (364 °C), denoting its higher structural stability and less degradation within its structure. This was further supplemented by the greater similarities of the IR spectrum of DES chitin to commercial chitin, compared to acid-base chitin. However, the chitin yield from DES process (7.23±4.47) was significantly less compared to the chitin yield from acid-base process (11.03±4.31) and literature values (11.67).